Applying Titius-Bode’s Law on Exoplanetary Systems - M. B. Altaie; Z. Yousef; A. I. Al-Sharif (Jordan Journal of Physics, 2025)
We report the application of Titius-Bode’s law on 43 exoplanetary systems containing four or more planets. Due to the fact that most of these systems have their planets located within compact regions extending for less than the semi-major axis of Mercury, we found the necessity to scale down the Titius-Bode’s law in each case. In this paper, we present sample calculations for three systems out of the whole set. Results show that most systems studied are verifying the applicability of the law with high accuracy. Consequently, our investigation verifies practically the scale invariance of Titius-Bode’s law. The results of this study buildup the confidence in predicting positions of the exoplanets according to Titius-Bode’s law besides enabling diagnosing possible reasons of deviations. Keywords: Titius-Bode’s law; Exoplanets; Scale invariance.